Evidence on delay in sexual initiation, multiple partnerships and condom use among young people : review of Caribbean HIV behavioural studies (2013)
Discusses evidence which shows that there are substantial levels of early sexual initiatiion, intergenerational sex among females and multiple partnerships among males, in which condom use is inconsistent.
Keywords: HIV